Continuous 24-Hour Leptin, Proopiomelanocortin, and Amino Acid Measurements in Human Cerebrospinal Fluid: Correlations With Plasma Leptin, Soluble Leptin Receptor, and Amino Acid Levels - Wardlaw, Sharon L. (Endocrine Society, 2014)
CONTEXT: In order to characterize diurnal changes in central leptin and its target neuropeptide, proopiomelanocortin (POMC), we measured leptin and POMC in cerebrospinal fluid (CSF) as related to changes in plasma leptin and soluble leptin receptor (sOB-R) levels. CSF and plasma levels of 20 amino acids (AA) were also measured because AA can affect brain POMC. DESIGN AND PARTICIPANTS: Stored CSF and plasma samples obtained from eight healthy subjects who served as controls for a previous study were evaluated. CSF was collected hourly over 33 h via indwelling subarachnoid catheter. Leptin, sOB-R, and POMC were measured by sensitive ELISA and AA by gas chromatography-mass spectrometry. RESULTS: There was a diurnal rhythm for plasma leptin with a peak at 2200 h (144% of baseline) and there was a similar diurnal rhythm for CSF leptin with a peak (117%) 3–5 h after the plasma peak. Plasma sOB-R was lowest at 0300 h and correlated negatively with plasma and CSF leptin. A diurnal rhythm for POMC in CSF was also detected with a peak (125%) at 0100 h. A positive correlation existed between CSF POMC and leptin in individual subjects over time. CSF levels of many AA increased at night. There was a significant correlation between CSF POMC and 10 AA, including leucine, isoleucine, tryptophan, and tyrosine. CONCLUSIONS: Diurnal changes occur in leptin and POMC in human CSF that likely reflect changes in central leptin and melanocortin activity. Our results suggest that nocturnal elevations in leptin, AA, and POMC may help to suppress appetite and feeding at night.